“Entre lírios e delírios”: a (des)institucionalização e as (re)invenções do feminino na saúde mental de Sorocaba - Momberg, Thaiga (2018)
The present study sought to investigate the specificities of women in the process of deinstitutionalization in the city of Sorocaba/SP, considering how gender issues are articulated with their tutelage and / or independence. It also sought to understand how the women currently living in the Therapeutic Residences Services (SRTs in Portuguese) experience their independence, taking into account all the historical silencing experienced by institucionalized women and the stigma of the madness attributed to them. Participant observation and interviews were carried out in two SRTs where these women live. The bibliography used showed that female sexuality is a locus of control across history, bringing an interface with madness. The results demonstrated devices of control of sexuality and femininity in the asylum, and also outside them, leading to the infantilization and tutelage of the residents. From this, it is necessary to intersect the discussion of the thematic, problematizing the peculiarities about femininity, considering the questions strongly present regarding gender, race and class.